Level of medication adherence and its determinants of cardiovascular disease patients attending at specialized teaching hospitals of Amhara regional state, Ethiopia: a multicenter cross-sectional study - Dagnew, Samuel Berihun; Wondm, Samuel Agegnew; Dagnew, Fisseha Nigussie; Yimer, Yohannes Shumet; Wondmkun, Yehualashet Teshome; Moges, Tilaye Arega (Frontiers in Pharmacology, 2024)
Non-adherence to medication in patients with cardiovascular disease continues to be a main cause of suboptimal management, increased morbidity and mortality, and increased healthcare expenses. The present study assessed the level of medication adherence and its determinants of cardiovascular disease patients.An institutional-based multicenter cross-sectional study was conducted with patients with cardiovascular disease in Northwest Ethiopian teaching hospitals. The level of medication adherence was evaluated using a standardized questionnaire of the Adherence in Chronic Disease Scale (ACDS). To find determinants of the level of medication adherence, an ordinal logistic regression model was employed. Statistics were significant when P ≤ 0.05 at a 95% confidence interval (CI).In the end, 336 participants were included in the research.